2023
DOI: 10.1002/agj2.21320
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Random Forest to Bayesian Networks as nitrogen management decision support systems

Abstract: Nitrogen (N) is notoriously difficult to manage and there are many approaches for fertilizer N rate recommendations. Existing fertilizer N rate recommendation systems can be improved by incorporating the effects of weather on sidedress economicoptimum N rates (EONR). In this study, we evaluated the performance of machine learning methods, a Bayesian Network (BN) and a Random Forest (RF) for estimating EONR for corn. BN draws relationships between variables based on assumptions about conditional independence, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…Changes in PSNT N rate recommendations caused by sample handling were generally quite small (Table 3). Sulik et al (2023) noted that N DSS accuracy is best assessed using the frequency of N recommendations within an acceptable net return range and classified N rate recommendations based on whether they could predict an N rate within $25 ha −1 of the maximum N return (i.e., the economically optimum N rate). Using Ontario corn and fertilizer price data as well as yield response curves from 2010 to 2020, they identified that N rates within 46 kg N ha −1 of the economically optimum N rate were sufficient to avoid losses >$25 ha −1 in all tested cases.…”
Section: T a B L Ementioning
confidence: 99%
“…Changes in PSNT N rate recommendations caused by sample handling were generally quite small (Table 3). Sulik et al (2023) noted that N DSS accuracy is best assessed using the frequency of N recommendations within an acceptable net return range and classified N rate recommendations based on whether they could predict an N rate within $25 ha −1 of the maximum N return (i.e., the economically optimum N rate). Using Ontario corn and fertilizer price data as well as yield response curves from 2010 to 2020, they identified that N rates within 46 kg N ha −1 of the economically optimum N rate were sufficient to avoid losses >$25 ha −1 in all tested cases.…”
Section: T a B L Ementioning
confidence: 99%